UM FRAMEWORK MULTIAGENTE PARA A PERSONALIZAÇÃO DA WEB BASEADO NA MODELAGEM DE USUÁRIOS E NA MINERAÇÃO DE USO - Marinho, Leandro Balby (2005)
With the continuous migration of a great diversity of services to the Web, the need for characterizing the users in this environment increases. For that, components that can continually perceive their environment and rapidly adapt to its changes are required, thus reflecting the changes in the user behaviors. Among the existent approaches for modeling Web users, Web usage mining appears as one of the most interesting. Through Web usage mining a user can be implicitly and automatically modeled through his/her usage data, generated from his/her interaction with the Web. This work proposes ONTOWUM, a user modeling and usage mining-based multi-agent framework for Web personalization. The framework comprises two layers, where four agents are distributed according to their responsibilities: Interface agent, responsible for both capturing the user browsing information and performing the adaptation effects; User Modeling agent, responsible for creating and updating both user models and adaptation models; Acquirer agent, responsible for creating and updating an usage data repository containing past user models; and finally, Miner agent, responsible for both discovering group of users with similar browsing behavior and classifying the current user in these groups. The Interface and User modeling agents belong to the user information-processing layer, and the Acquirer and Miner agents belong to the pattern-discovering layer. The methodology and tool used to guide the analyses and design phases were MADEM ( Multi-Agent Domain Engineering Methodology ) and ONTOMADEM, respectively. For the implementation of ONTOWUM it was used the JADE framework.